Influence Of Machining Parameters On Surface Roughness And Quality Of Hole In Drilling Of CFRP Composites With Ultrasonic Machine - Ali Al-Baiti, Mohammed Hasan (2019)
Carbon fiber reinforced composite materials are used in a variety of engineering applications due to their significant properties. Armor steel composites are used in areas of application such as military vehicles, tanks, cars, etc. Currently, composites are used to replace conventional metallic materials in a wide range of industries, including aerospace, aircraft, and defense, which require high strength- to- weight and stiffness- to- weight structural materials. Due to their high mechanical properties, CFRP composites are used in fairings, passenger compartments, and storage room doors. Of all the processing operations, drilling is the most commonly used operation. However, the drilling of these composite materials, regardless of the area of application, can be considered a critical operation due to their tendency to delaminate when mechanically stressed. It is therefore important to understand the drilling behavior by conducting a large number of drilling experiments and by screening drilling parameters such as feed rate, spindle speed, ultrasonic and with or without using submersible. These composites provide corrosion resistance. The influence of machining parameters on surface roughness and quality of hole in the drilling of CFRP composites with an ultrasonic machine is investigated in detail